HUBUNGAN POLA MAKAN DENGAN KEJADIAN SINDROM DISPEPSIA PADA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS SUMATERA UTARA TAHUN 2015 - Novita Kurniati Nasution; Evawany Y Aritonang; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
The risk of disease caused by the wrong eat’s pattern or unhealthy these days tend to increase Most students experience a variety of diseases caused by the wrong diet, which are experiencing gastrointestinal disorders, such as dyspepsia. This research was conducted on the majority of students are 100 students in the Faculty of Public Health, University of North Sumatra. This study used a cross-sectional design with observational studies / observation moment. Collecting data through interviews using a questionnaire. This study aims to know the relationship diet and the incidence of dyspepsia syndrome in students of the Faculty of Public Health, University of North Sumatera. The result showed most students have irregular eating schedule as many as 61% of students. Most students consume food and drinks that irritating as many as 59% of students. from the 6% students at irregular eating schedule contained 84% of students who experience dyspepsia syndrome, whereas of the 39% students on a regular eating schedule contained 67% of students who did not experience dyspepsia syndrome. There is a relationship between eating schedule with the incidence of dyspepsia syndrome based on chi-square test with P = 0.001. from the 59% students who consume foods and beverages irritating there is 75% of the students who have dyspepsia syndrome and of the 41% students who consume this type of food that is not irritating contained 51% of students who did not experience dyspepsia syndrome. There is a significant relationship between the type of food and drink with the incidence of dyspepsia syndrome in public health university North Sumatra students, based on chi-square test with a P value = 0.008. It is recommended that the Faculty of Public Health, University of North Sumatra can provide healthy cafeteria so students can set an eating schedule and reduce the consumption of food and beverages is irritating to avoid the syndrome of dyspepsia. Keywords: dietary habit, students, syndrome of dyspepsia